2021
DOI: 10.7150/ijms.62467
|View full text |Cite|
|
Sign up to set email alerts
|

PRMT4 promotes hepatocellular carcinoma progression by activating AKT/mTOR signaling and indicates poor prognosis

Abstract: Background: Protein arginine methyltransferase 4 (PRMT4) has been reported to play a role in several common cancers; however, the function and mechanism of PRMT4 in hepatocellular carcinoma (HCC) are not fully understood. This study aimed to investigate the role and mechanism of PRMT4 in the progression of HCC. Methods: PRMT4 expression and clinicopathological characteristics were investigated using an HCC tissue microarray (TMA) consisting of 140 patient samples analyzed by immunohistochemistry. CCK-8, crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…CARM1 was previously reported to suppress the glycolysis in liver cancer cells by mediating arginine 234 (R234) methylation of GAPDH, thus inhibiting the proliferation of liver cancer cells 12 . This con icts with another study demonstrating that CARM1 indicates poor prognosis and promotes HCC progression by activating AKT/mTOR signaling 13 . These con icting results lead to a confused understanding of CARM1's functions in HCC, thus needing to explore its underlying molecular mechanism.…”
Section: Introductionsupporting
confidence: 50%
See 1 more Smart Citation
“…CARM1 was previously reported to suppress the glycolysis in liver cancer cells by mediating arginine 234 (R234) methylation of GAPDH, thus inhibiting the proliferation of liver cancer cells 12 . This con icts with another study demonstrating that CARM1 indicates poor prognosis and promotes HCC progression by activating AKT/mTOR signaling 13 . These con icting results lead to a confused understanding of CARM1's functions in HCC, thus needing to explore its underlying molecular mechanism.…”
Section: Introductionsupporting
confidence: 50%
“…CARM1 functions as an oncogene or a tumor suppressor depending on cancer types 16,17 . However, the roles of CARM1 in dynamic HCC progression are controversial 12,13 . We analyzed the HCC cohort in TCGA and found that HCC patients at the advanced stages expressed higher CARM1 than early staged patients (stage III + IV vs stage I + II) (Fig.…”
Section: Carm1 Suppresses Hcc Metastasis In a Trim47dependent Mannermentioning
confidence: 99%
“…revealed proteins that can interact directly with CARM1 and proteins with arginine methylation sites, but PFK1 and PFKFB3 were not among these proteins. AKT and AMPK are able to activate PFK1 and PFKFB3 when they exert kinase activity, 22,39,40 and both kinases can be regulated by CARM1 41,42 . To decipher the molecular mechanisms by which CARM1 regulates cellular metabolism, transcriptomic assays were performed on Carm1 ‐OE MC3T3E1 cells (Figure S4a), and the results showed that the osteogenesis‐related genes Spp1 and Ocn and several members of the Col1 family had up‐regulated expression in the Carm1 ‐OE group.…”
Section: Resultsmentioning
confidence: 99%
“…AKT and AMPK are able to activate PFK1 and PFKFB3 when they exert kinase activity, 22 , 39 , 40 and both kinases can be regulated by CARM1. 41 , 42 To decipher the molecular mechanisms by which CARM1 regulates cellular metabolism, transcriptomic assays were performed on Carm1 ‐OE MC3T3E1 cells (Figure S4a ), and the results showed that the osteogenesis‐related genes Spp1 and Ocn and several members of the Col1 family had up‐regulated expression in the Carm1 ‐OE group. Subsequent Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis showed that the PI3K–AKT signalling pathway was one of the main enriched pathways with differentially expressed genes (Figure 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…The original version of our article 1 unfortunately contained an error in Figure 3 E. The picture of Huh7 cell invasion assay picture in the sh2 group in Figure 3 E was incorrectly assembled. We sincerely apologize for this error.…”
mentioning
confidence: 99%